Colossal Dance Sawah Solok: Heritage in the Heart of the City: Artistic Creation Based on Agrarian Activities and Food Security - Emri Emri; Susas Rita Loravianti; M Halim (Pascasarjana Institut Seni Indonesia Padang Panjang, 2025)
This study examines the creation of the colossal dance Sawah Solok: Heritage in the Heart of the City as an artistic response to agrarian life and food security in Solok City, West Sumatra. Employing a practice-based research approach, the study positions dance creation as a form of cultural knowledge production rooted in local agricultural practices. The research aims to analyze how agrarian activities—such as rice cultivation, field maintenance, and harvest traditions—are transformed into choreographic structures that articulate social values, collective memory, and cultural resilience. Data were generated through field observations in urban rice fields, interviews with farmers and cultural actors, documentation of the creative process, and reflective analysis by the choreographer. The creative process follows Alma M. Hawkins’ stages of exploration, improvisation, and formation, enabling embodied experiences of agrarian labor to be translated into movement vocabulary, spatial design, and performance structure. The findings reveal that food security is represented not merely as an economic issue, but as a cultural and ethical commitment embedded in communal cooperation and adat values. This study contributes to contemporary dance discourse by demonstrating how agrarian practices and food security narratives can be integrated into colossal dance performances situated in public space.